Perilaku Pekerja Seks Komersial Terhadap Pencegahan Penyakit Menular Seksual Di Lokalisasi Kalinyamat Bandungan - Triwik Sri Mulati (Poltekkes Kemenkes Surakarta, 2016)
Abstract: Behavior, Commercial sex workers, Sexually transmitted diseases. This study aims to reveal the phenomenon of Conduct Against Commercial Sex Workers Sexually Transmitted Disease Prevention at Localization Kalinyamat, Bandungan. This study used a qualitative design with sample collection technique is purposive sampling with maximum sampling type of sampling variation. The collection of data by using a technique Focus Group Discussion (FGD) and In-depth Interviews (WM). In this study, researchers used informants DKT 6 and 8 informants WM. Test the validity of the data was done by using triangulation. The results showed that the behavior of prostitutes on the prevention of STDs seen from most of the knowledge already know about the definition, causes, types, signs and symptoms of STD prevention, of attitudes that are divided into several categories there who agree and disagree, on the activities on the prevention largely meet health standards.